2004
DOI: 10.2337/diacare.27.7.1591
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lower-Extremity Disease in the U.S. Adult Population ≥40 Years of Age With and Without Diabetes

Abstract: OBJECTIVE—Although lower-extremity disease (LED), which includes lower-extremity peripheral arterial disease (PAD) and peripheral neuropathy (PN), is disabling and costly, no nationally representative estimates of its prevalence exist. The aim of this study was to examine the prevalence of lower-extremity PAD, PN, and overall LED in the overall U.S. population and among those with and without diagnosed diabetes. RESEARCH DESIGN AND METHODS—The analysis consisted of data for 2,873 men and women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
357
5
19

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(403 citation statements)
references
References 41 publications
22
357
5
19
Order By: Relevance
“…23 Clairotte et al 12 recently validated oscillometric ABI measurement in diabetic patients and reported lower correlation coefficients (r¼0.49 vs. 0.60) and higher differences between the two methods (0.03±0.25 vs. 0.01±0.28) in diabetics compared with non-diabetics. In contrast, the findings of this study did not differ with regard to the presence of diabetes, and the diagnostic performance of the oscillometric method was similar in diabetics and non-diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…23 Clairotte et al 12 recently validated oscillometric ABI measurement in diabetic patients and reported lower correlation coefficients (r¼0.49 vs. 0.60) and higher differences between the two methods (0.03±0.25 vs. 0.01±0.28) in diabetics compared with non-diabetics. In contrast, the findings of this study did not differ with regard to the presence of diabetes, and the diagnostic performance of the oscillometric method was similar in diabetics and non-diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral neuropathy is a highly prevalent condition, particularly in older populations 1, 2, 3. This disease affects patients by causing pain, decreased quality of life, falls, ulcerations, and amputations 3, 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…1 In particular, PAD is a strong predictor of subsequent cardiovascular morbidity and mortality as a result of concomitant coronary artery and cerebrovascular disease. 1,2 Patients with PAD have a threefold higher risk of myocardial infarction, stroke and death than those without PAD. 3 As a consequence of the Western lifestyle, the prevalence of PAD is high in industrialized countries.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of PAD include intermittent claudication or rest pain. 1 However, more than 50% of PAD patients are symptomless. 4 Thus, PAD remains largely underdiagnosed and undertreated.…”
Section: Introductionmentioning
confidence: 99%